Physical activity among adults in Canada: an intersectional analysis of immigrant and socioeconomic status - Eun-Young Lee; Heejun Lim; Roman Pabayo; Asaduzzuman Khan (Discover Social Science and Health)
Abstract Background Physical activity (PA) participation during the COVID-19 pandemic may vary across different population groups. This study examined the associations between immigrant status, socioeconomic status (SES), and outdoor/indoor PA. Methods National-level, cross-sectional data from 4,383 Canadians aged 25 + yrs (51% women) who participated in the Canadian Perspective Survey Series–Impacts of COVID-19 were used. Exposure included immigrant status with potential effect modifiers—educational attainment, employment status, and financial impacts due to the COVID-19 pandemic. Outcome included outdoor and indoor PA. Covariates included sex, age, household size, presence of a child < 18 yrs, marital status, and changes in unhealthy behaviors (e.g., alcohol, tobacco, junk food, screen time) during the pandemic. Results About a quarter (24%) of the participants were immigrants who participated in less outdoor PA but more indoor PA than their Canadian-born counterparts (outdoor PA: 42% vs 70%; indoor PA: 68% vs 56%, respectively). Regardless of education, employment, and financial impacts, immigrants to Canada were far less likely to participate in outdoor PA than their Canadian-born counterparts during the COVID-19 pandemic. For indoor PA, immigrants, particularly those unemployed or financially impacted, were more likely to report participating in indoor PA than Canadian-born individuals. Among Canadian-born individuals, post-secondary education and employment status (employed but absent from work) have emerged as key correlates for both outdoor and indoor PA. Conclusions The findings highlight the importance of understanding the differential SES factors influencing outdoor and indoor PA participation among immigrants and Canadian-born individuals living in Canada. Future research should investigate ways that could equitably promote access to outdoor PA.